In vitro alpha-glucosidase and alpha-amylase enzyme-inhibited activities by water-lily (Nymphaea genus) extracts - Korawinwich Boonpisuttinant,; Supanida Winitchai,; Purin Akkarakultron,; Sarinporn Udompong, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Chalong Kwan (C), Khao Mongkol (K) and Chompoo Mameaw (P) are the water-lily in the family of Nymphaeaceae which were planted in Thailand. In this study, leaves (1), flowers (2), tuber (3), pollen (4), branches (5) of the three water-lily were boiled with distilled water (W) and macerated on 95% ethanol (E). The extracts from water-lily including C3-E, P1-E, P3-E, C1-W, P1-W, P3-W, and P5-W were showed the highest level of free radical scavenging activities measured by (DPPH) assay (SC50 range of 0.003-0.007), which is more than L-ascorbic acid (SC50 of 0.013 ± 0.0001 mg/mL) about four times. The effect of anti-diabetic was determined inhibitory activities of α-glucosidase and α-amylase by enzymatic assay. P4-E extract was the highest exhibited the α-amylase activities (AC50 of 0.02 ± 0.001 mg/mL) with higher than acarbose for ten times (AC50 of 0.23 ± 0.14 mg/mL). Whereas, the C2-E, C3-E, and C1-W extracts inhibited the activity of α-glucosidase (GC50 range of 0.08-0.11), which higher than acarbose for 6 times (GC50 of 0.63 ± 0.04 mg/mL). The ethanol extracts from Chompoo Mameaw (P1-E and P3-E) which demonstrated the highest antioxidant and anti-diabetic activity, might be possible for further development to natural products for diabetic patients.